2016
DOI: 10.1186/s40795-016-0111-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutrition education on recurrent coronary events after percutaneous coronary intervention: A randomized clinical trial

Abstract: Background: Changes in lifestyle include a healthy diet. However, due to different educational approaches, the effects of nutritional counselling are still not very encouraging and require further study. The objective of this study was to analyse the effectiveness of a nutrition education intervention program on mortality and recurrence of cardiovascular events evaluated after one and four years of follow-up. Methods: A randomized clinical trial was performed at a public hospital in Brazil with 200 patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…If there is a change in the lifestyle of the patients, this change should also happen in the diet of the people. In Vieira et al ( 2016) study, the results of one year and four years after the follow-up showed that although the difference in the primary and secondary outcomes under the educational program in the two studied groups was not significant, the program was associated with a reduction in complications and outcomes (21).…”
Section: Health Components Agementioning
confidence: 90%
“…If there is a change in the lifestyle of the patients, this change should also happen in the diet of the people. In Vieira et al ( 2016) study, the results of one year and four years after the follow-up showed that although the difference in the primary and secondary outcomes under the educational program in the two studied groups was not significant, the program was associated with a reduction in complications and outcomes (21).…”
Section: Health Components Agementioning
confidence: 90%
“…One feasible alternative to target this health deterioration is educating the community and encouraging healthy lifestyle modifications through educational activities [1][2][3][4]. According to various studies, educational outreach activities are more valuable when associated with real-world settings while employing a community-based participatory approach [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…One proposal to the above query is educational movements such as outreach-oriented activities. Health-related educational activities can diminish risk elements associated with heart disease and improve overall health [14], can promote healthy body weight [1], and lessen the occurrence of obesity, nutritional deficiency, and diabetes [15][16][17]. Further, health-related educational outreach activities can improve physical activity levels and have promising results when performed in real-world settings using a community-based participatory approach [18][19][20].…”
Section: Introductionmentioning
confidence: 99%